‘Cooking’ Masculinity in The Digital World: A Look at @Amerix’s #MasculitySaturday (Mwanga wa Lugha, 2024)
Through technology, the digital world has birthed a new space where people can connect with each other. This space has resulted in a shift where concepts are no longer static but constantly shifting. One of these concepts is masculinity. A social construct, the concept of what constitutes masculinity continues to shift as the digital world moves towards both diversity and inclusivity. This paper seeks to explore how a medical consultant, Eric Amunga, has appropriated the digital space to make commentary on various social aspects. Using his Twitter handle @amerix, Amunga runs #MasculinitySaturday, whose ‘teachings’ range from health, relationships, sex to parenting, all in a bid to ‘equip’ men with means with which to navigate manhood. With a following of over 1.2 million followers, this article argues that Amunga has not only created a platform for his ‘teachings’ but also an avenue for the world to engage. Through the ‘replies’ section, members are allowed to comment on the topical issues thus engaging in debate. I thus examine the aesthetics of this discourses and demonstrate how Amunga draws in, engage and sustains his following through New Media and how this relates to the postcolonial experience of the contemporary period in East Africa.